Illicit Drugs in Modern China : Production, Trafficking and Consumption - Morozova, Aleksandra (fi=Turun yliopisto|en=University of Turku|, 2018)
The topic of the research is production, trafficking and consumption of illicit drugs in modern day China. The subject of this research is recent and current trends in illicit substances production in China and in the neighbouring countries, trafficking routes and trends, and drugs consumption rates. The purpose of this research is to compile an overall overlook on the drug-related issues in China, describe the major recent trends in illicit drug trafficking and consumption, precursor production and export, and underline the results and the shortcomings of the existing drug enforcement in the PRC. The research is completed by the methods of conducting qualitative empirical study, mainly via extended structured interviews, open-ended questions questionnaire and a survey using “Likert Scale”, combined with the collection, structuralizing and analysis of secondary data from numerous Academic studies, international organizations such as United Nations Office on Drugs and Crimes reports, media outlets etc. The key results of the study are presented in providing the broad and structured perspective on the current drug production, trafficking and consumption trends in China, along with providing a substantial insight on the Chinese metropolises situation in context of illicit drugs. Furthermore, the important result of the study is the contrast of the findings to the current official rhetoric of Chinese officials concerning drug-related issues in the PRC recently. China notoriously has been fighting with the burden of drug trafficking and addiction for many years now, and the current trends in this context still seem to be quite daunting. Located between the two main drug producing areas of Asia, the “Golden Triangle” and the “Golden Crescent”, having an immense chemical production industry, seemingly not sufficiently regulated, and ostensibly feeble drug enforcement, China still suffers from overwhelming and rising drug trafficking and consumption rates, despite the facade maintained by Chinese officials and commonly acknowledged notion of China having strict control over drugs.